2019
DOI: 10.1055/a-0929-6603
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided gallbladder drainage versus percutaneous cholecystostomy for high risk surgical patients with acute cholecystitis: a systematic review and meta-analysis

Abstract: Background Recent evidence suggests that endoscopic ultrasound-guided gallbladder drainage (EUS-GBD) is an effective and safe alternative to percutaneous drainage (PT-GBD). We conducted a systematic review and meta-analysis to compare these two procedures in high risk surgical patients with acute cholecystitis. Methods A comprehensive electronic literature search was conducted for all articles published up to October 2017 to identify comparative studies between EUS-GBD and PT-GBD. A meta-analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 25 publications
5
62
0
4
Order By: Relevance
“…Hence, the use of LAMS is of paramount importance, as the lumen apposing force generated by LAMS is significantly higher than that of other types of stents 25. The safety of the EUS-guided anastomosis is confirmed by the results of the meta-analyses and a few large-scale studies 24 26. In fact, the occurrence of an anastomotic leak after successful placement of a LAMS for acute cholecystitis is exceedingly rare.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Hence, the use of LAMS is of paramount importance, as the lumen apposing force generated by LAMS is significantly higher than that of other types of stents 25. The safety of the EUS-guided anastomosis is confirmed by the results of the meta-analyses and a few large-scale studies 24 26. In fact, the occurrence of an anastomotic leak after successful placement of a LAMS for acute cholecystitis is exceedingly rare.…”
Section: Discussionmentioning
confidence: 97%
“…Two studies reported lower readmission rates, three studies reported lower re-intervention rates and one study reported significantly lower 1 year adverse events rates. A meta-analysis then concluded that EUS-GBD also had fewer adverse events than PT-GBD (OR: 0.43; CI 0.18 to 1.00; p=0.05; I 2 =66%), shorter lengths of hospital stay, with pooled standard mean difference of −2.53 (95% CI: −4.28 to −0.78; p=0.005, I 2 =98%); required significantly less re-interventions (OR: 0.16; CI: 0.04 to 0.042; p=0.0002; I 2 =32%) resulting in significantly less unplanned readmissions (OR: 0.16; 95% CI: 0.05 to 0,53; p=0.003, I 2 =79%) 24. The findings of the current study are in-line with the all of the above studies.…”
Section: Discussionmentioning
confidence: 99%
“…EUS-guided gallbladder drainage (EUS-GBD), commonly used in treating acute cholecystitis in patients who are not surgical candidates, is an attractive salvage therapy when both ERCP and standard EUS-BD techniques are unsuccessful [7,8]. A previous single-center study reported a clinical success rate of 91 % for EUS-GBD in 12 patients who failed ERCP and EUS-BD, with an adverse event rate of 16.7 % [9].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis by Luk et al comparing 206 and 289 EUS-GBD and PT-GBD patients, respectively, found similar rates of technical and clinical success between the two procedures. 26…”
Section: Alternative Proceduresmentioning
confidence: 99%